Analyzing the critical success factors in the online-game development: a framework proposal using the Delphi-Topsis Method - Linares Barbero, Manuela (2023)
The online-game industry has increased exponentially in the last years, boosted by the global pandemic crisis, and it´s expected to continue growing. Moreover, specialized software (game engines) is used to develop online-games. This fast growth of both, online-game industry and game engines, shows the convenience for a better understanding of online-games´ development. Thus, this paper aims to define a critical success factors (CSF) framework in developing online-games, and it combines the Delphi and TOPSIS methodology. Concretely, its application follows. First, CSF were recognized from the literature. Second, they were verified by contacting software developers of the game engine Unity using Delphi methodology. Then, a numerical example of the TOPSIS methodology is shown. This method allowed to generate a framework of 21 critical factors, grouped in 3 dimensions: (1) Game content design, (2) Value added and (3) Game motivation. The results revealed that competition is the most important factor in the Social motivation construct. Also, Mission and tasks, and User interface are the most important factors in the Game content design dimension. Definitely, this framework provides a tool for decision making in the online-game development process.